Efficacy and cytotoxicity of a bleaching gel after short application times on dental enamel - Soares, Diana Gabriela [UNESP]; Ribeiro, Ana Paula Dias [UNESP]; da Silveira Vargas, Fernanda [UNESP]; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (Springer Nature, 2012)
Objectives: This study aimed to evaluate and correlate the efficacy and cytotoxicity of a 35 % hydrogen peroxide (HP) bleaching gel after different application times on dental enamel. Materials and methods: Enamel/dentin disks in artificial pulp chambers were placed in wells containing culture medium. The following groups were formed: G1, control (no bleaching); G2 and G3, three or one 15-min bleaching applications, respectively; and G4 and G5, three or one 5-min bleaching applications, respectively. Extracts (culture medium with bleaching gel components) were applied for 60 min on cultured odontoblast-like MDPC-23 cells. Cell metabolism (methyl tetrazolium assay) (Kruskal-Wallis/Mann-Whitney; α = 5 %) and cell morphology (scanning electron microscopy) were analyzed immediately after the bleaching procedures and the trans-enamel and trans-dentinal HP diffusion quantified (one-way analysis of variance/Tukey's test; α = 5 %). The alkaline phosphatase (ALP) activity was evaluated 24 h after the contact time of the extracts with the cells (Kruskal-Wallis/Mann-Whitney; α = 5 %). Tooth color was analyzed before and 24 h after bleaching using a spectrophotometer according to the Commission Internationale de l'Eclairage L*a*b* system (Kruskal-Wallis/Mann-Whitney; α = 0.05). Results: Significant difference (p < 0.05) in cell metabolism occurred only between G1 (control, 100 %) and G2 (60.6 %). A significant decrease (p < 0.05) in ALP activity was observed between G2, G3, and G4 in comparison with G1. Alterations on cell morphology were observed in all bleached groups. The highest values of HP diffusion and color alterations were observed for G2, with significant difference among all experimental groups (p < 0.05). G3 and G4 presented intermediate color change and HP diffusion values with no statistically significant differences between them (p > 0.05). The lowest amount of HP diffusion was observed in G5 (p < 0.05), which also exhibited no significant color alteration compared to the control group (p > 0.05). Conclusions: HP diffusion through dental tissues and its cytotoxic effects were proportional to the contact time of the bleaching gel with enamel. However, shorter bleaching times reduced bleaching efficacy. Clinical relevance: Shortening the in-office tooth bleaching time could be an alternative to minimize the cytotoxic effects of this clinical procedure to pulp tissue. However, the reduced time of bleaching agent application on enamel may not provide adequate esthetic outcome. © 2012 Springer-Verlag Berlin Heidelberg.
Keywords: Cytotoxicity; Odontoblasts; Tooth bleaching; Tooth color